Pengaruh Konsentrasi Pupuk Hayati Bioboost Terhadap Peningkatan Produksi Tanaman Selada (Lactuca sativa. L) - A. P Manuhuttu; Herman Rehatta; J.J.G Kailola (Faculty of Agriculture, Pattimura University, 2014)
Lettuce (Lactuca sativa L.)is one of hleafy vegetables that have high economic value in Indonesia and it gives good benef its ton the con sumers.The us of organic fertilizers is expected to be more optimal in agriculture today, considering the impact that the use of inorganic fertilizers may damage the soil and increasing environmental pollution with chemical residues in the soil, which result in decreased land productivity. This study aimed to determine the effect of Bioboost fertilizer to increase crop yield of lettuce. Treatment were arranged in a Randomized Block Design, with one factor namely the concentration of Bioboost fertilizer consisting of 7 treatments: B0=0 cc (control), B1= 20 cc, B2= 40 cc, B3= 60 cc, B4= 80 cc, B5=100 cc per liter of water, and B6 = 120 cc / liter of water, with 3 replications so that there were 21 experimental units. Each treatmental unit consisted of 8 plants so that overall there were 168 plant populations. These results indicated that concentration of Bioboost bio-fertilizers gave a significant effects on the growth of lettuce. Fertilizer cencentration of 80 cc / liter of water (B4) was the best concentration for growth and increased yield of lettuce.